Determining Factors Associated with Adolescents' Knowledge of the Impact of Early Marriage - Lilis Mamuroh; Rindayu Bidara Caela Nentika; Adelse Prima Mulya (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Early marriage continues to be a significant social issue with far-reaching consequences for adolescents, particularly in psychological, health, and economic domains. One of the key factors influencing early marriage is the level of adolescents’ knowledge. Adequate understanding of the impacts of early marriage is therefore essential in preventing the practice. This study aims to determine the determinants associated with adolescents' knowledge levels about the impact of early marriage at Junior Islamic School.Method: This was a descriptive analysis employing cross-sectional design. Population of the study were students at MTs Al Ishlah, and used total sampling technique. We included a total of 111 students. The validity test prove that value of r larger than r table (0.361), and the result of questionnaire reliability test was > 0.60 (α: 0.082). Data collection was carried out in May 2025 and was assisted by fellow researchers in each classroom.Result: The results of the analysis showed that most respondents were in the middle adolescent age category and were dominated by the male gender. The majority of respondents came from families with lower to middle parental education levels and income levels below the UMK. A correlation was found between several factors such as age, parents’ educational level, parental income, and the sources of information accessed by adolescents and their level of knowledge about the consequences of early marriage. This relationship was statistically significant, with a p-value of ≤ 0.05. It can be concluded that parental education level, parental income, information sources, and age are factors that are significantly related to the level of adolescent knowledge about the impact of early marriage. The implication of this study is the need for direct educational intervention programs by health workers or schools by considering determinant factors to be able to increase adolescent knowledge.